PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH SEBAGAI UPAYA MENGHASILKAN PRODUK HUKUM RESPONSIF - Ida Ayu Putu Widianti; Luh Putu Suryani; Ketut Adi Wirawan (Jurnal Hukum Saraswati (JHS), 2019)
The era of regional autonomy provides an opportunity for each regional government to regulate its own households except for matters that are the authority of the central government. The form of regulation carried out by the regional government is by issuing legislation in the form of regional regulations. The regional regulations created should be able to accommodate the needs and interests of the community, so that the goal of regional autonomy, namely the welfare of the people in the region, can be realized. The research method is normative legal research. Legal materials in the form of primary, secondary and tertiary legal materials. Qualitative legal materials collected will be sorted, analyzed and then presented in a descriptive form in the form of a research report as referred to in this study. The results of this study indicate that through participatory methods, the substance of the regulations in regional regulations can accommodate the interests, needs and values of the community. The next implication is the high obedience of community law to regional regulations and the attainment of the nature of the existence of law that is creating order and happiness in society.